Effects of two-months balanced diet in metabolically healthy obesity: lipid correlations with gender and BMI-related differences. Issue 1 (December 2015) - Rondanelli, Mariangela; Klersy, Chaterine; Perna, Simone; Faliva, Milena; Montorfano, Gigliola; Roderi, Paola; Colombo, Irma; Corsetto, Paola; Fioravanti, Marisa; Solerte, Sebastiano; Rizzo, Angela
Abstract Background Nowadays no researches has been performed on fatty acid profile (FA) and desaturase activity in metabolically healthy obesity (MHO). The aim of this study was to assessed gender and BMI-related difference in FA, estimated desaturase activities and the efficacy on metabolic changes produced by 2-months well-balance diet in MHO subjects. Methods In 103 MHO subjects (30/73 M/F; age:42.2 ± 9.5) FA, estimated desaturase activity, body composition (by DXA), Body Mass Index (BMI), lipid profile, adipokines (leptin, adiponectin, grelin, glucagon-like peptide-1), insulin resistence (by Homestasis metabolic assessment), C-reactive proteine, Atherogenic index of plasma (AIP) and Body Shape Index (ABSI) have been assessed. Gender and BMI related difference have been evaluated and the efficacy produced by 2-months well-balance diet has been considered. Results At baseline, obese subjects, compared to overweight, show a significantly higher oleic (p  <0.050), monounsaturated fatty acids (p  <0.040), C18:0 delta-9 desaturase activity (D9D) (p  <0.040) and lower linoleic acid (p  <0.020), polyunsaturated fatty acids (p  <0.020) and n-6 LCPUFA (p  <0.010). Concerning gender-related difference, women show a significantly higher arachidonic acid (p  <0.001), polyunsaturated fatty acids (p  <0.001), n-6 LCPUFA (p  <0.002), and lower monounsaturated fatty acids (p  <0.001), D6D activity (p  <0.030), C18:0 D9D (0.000) and C16:0 D9D (p  <0.030). The 2-months diet was associated with a significantly increase in arachidonic acid (p  = 0.007), eicosapentaenoic acid (p  = 0.030), docosahexaenoic acid (p  <0.001), long chain omega 3 polyunsaturated fatty acids (n-3 LCPUFA) (p  <0.001), delta-5 desaturase activity (D5D) (p  = 0.002), glucagon like peptide-1 (p  <0.001) and a significant decrease in palmitoleic acid (p  = <0.030), n-6/n-3 LCPUFA (p  <0.001), insulin resistance (p  = 0.006), leptin (p  = 0.006), adiponectin (p  <0.001), grelin (p  = 0.030), CRP (p  = 0.004), BMI (p  <0.001) and android fat mass (p  <0.001). Conclusions The balanced diet intervention was effective in improving metabolic indices.